(untitled) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2025)
This study initiates a philosophical exploration of Friedrich Nietzsche’s discourse on power dynamics, applying his critical framework to contemporary debates surrounding the digitization and algorithmization of society amid rapid advancements in robotics and artificial intelligence (AI). By engaging with Nietzsche’s conception of creative culture as a realm of autonomous thought and action, the analysis underscores the centrality of human agency and responsibility in sustaining social resilience. Nietzsche’s critique of metaphysical systems through the lens of power relations suggests that humanity can transcend systemic illusions via reason—understood not as passive rationality but as an active, critical reflection cultivated within creative cultural practices. Building upon Nietzsche’s dialectic of “weak and strong types of behavior,” this article proposes that his philosophy offers alternative ethical considerations for technological development. Specifically, it examines how resistance—manifested in creative and individualized cultural expressions—can counteract the mechanization of social existence. This resistance fosters ethical frameworks grounded in personal autonomy, emotional depth, and moral responsibility, challenging the homogenizing effects of algorithmic governance. Furthermore, the study highlights the significance of subjective narratives, emotional intelligence, and empathetic engagement in shaping human-centered ethics that safeguard individual experiences against systemic dehumanization. Ultimately, Nietzsche’s insights provide a robust philosophical foundation for rethinking digital ethics, advocating for a balance between technological progress and the preservation of human creativity and diversity.